World Orchid collections 2020 - Hermans, Johan; Hermans, Clare; Linsky, Jean; Li, Chia-Wei (Taiwan Orchid Growers Association (TOGA), 2020)
This volume...is the investigation of orchids in ex situ conservation collections around the world with an aim to understand and document conservation activities and acknowledge the contribution of individuals and organizations to orchid conservation. -- Introduction
Includes bibliographical references (p. 10)
TOGA and the 23rd World Orchid Conference -- KBCC & BGCI -- Editors' introduction : Methods ; The collections ; The Orchids ; The missing genera ; Orchid conservation -- Acknowledgements -- References -- Map of the 31 Project Rooting participants -- The Collections : Dr. Cecilia Koo Botanic Conservation Center, Taiwan ; Missouri Botanical Garden, Africa & Madagascar ; Durban Botanic Gardens, South Africa ; Atlanta Botanical Garden, U.S.A. ; University of California Botanical Garden at Berkeley, U.S.A. ; Huntington Botanical Gardens, U.S.A., Longwood Gardens, U.S.A. ; San Diego Zoo Orchid Collection, U.S.A. ; Orchid Species Preservation Foundation, Edmonton, Canada ; Montral Botanical Garden, Canada ; Lankester Botanical Garden, Costa Rica ; Botanical Garden of Quito, Ecuador ; Botanical Garden of the Soconusco Region & Orchidarium 'Santo Domingo,' Mexico ; Orchid Gardens of Inkaterra Machu Picchu Pueble Hotel, Peru ; Shanghai Chenshan Botanical Garden, China ; Xishuangbanna Tropical Botanical Garden, China ; Kadoorie Farm and Botanic Garden, Hong Kong, China ; Tsukuba Botanical Garden, Japan ; Gardens by the Bay, Singapore ; Singapore Botanic Gardens, Singapore ; Queen Sirikit Botanic Garden, Thailand ; Dunedin Botanic Garden, New Zealand ; Botanical Garden, University of Vienna, Austria ; National Botanic Gardens, Glasnevin, Dublin, Ireland ; Jardin du Luxembourg, Paris, France ; Berggarten of the Royal Herrenhausen Gardens, Hannover, Germany ; Munich Botanical Garden, German ; Gothenburg Botanical Garden, Sweden ; Royal Botanic Gardens, Kew, U.K. ; RHS Garden Wisley, U.K. ; Writhlington School Orchid Project, U.K. -- Table of natural general -- Abbreviations of contributing collections -- Natural general in contributing collections -- Hybrid general in contributing collections